6(x-3)=32

Simple and best practice solution for 6(x-3)=32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-3)=32 equation:


Simplifying
6(x + -3) = 32

Reorder the terms:
6(-3 + x) = 32
(-3 * 6 + x * 6) = 32
(-18 + 6x) = 32

Solving
-18 + 6x = 32

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 6x = 32 + 18

Combine like terms: -18 + 18 = 0
0 + 6x = 32 + 18
6x = 32 + 18

Combine like terms: 32 + 18 = 50
6x = 50

Divide each side by '6'.
x = 8.333333333

Simplifying
x = 8.333333333

See similar equations:

| 10x+43=273 | | (0.3+2x)(0.7+2x)=7.12 | | 7(r)=4*3.14*r^2 | | 1-100w^2=0 | | A(r)=4*3.14*r^2 | | 5x+8=7x+4 | | 5x^2+21=-22x | | 73-7x=2x+23 | | 100w^2-1=0 | | 5-6(x-5)=x | | 15x+y=50 | | 2.40/10=244/12 | | X/8-1=-6 | | 150=7x+3 | | 6x-10=2x+11 | | 3x+15=5x-10 | | 2x+3=8+3x | | 77-2x=6x+21 | | z^2+11x+10=0 | | 9-2(x-5)=12 | | 2/3x+16=20 | | 9+5(x-5)=12 | | 4x+22=30 | | x^2(3+2x)-3(6x+9)=0 | | 6g+3=-(2g+9) | | 0=-42-35r-7r^2 | | 4x+7x+5x=96 | | (2x+1)(2x+1)-9=40 | | 25-(4g+5)=-11 | | y=3y-3 | | (4xy-3xy)= | | -4+3x-6=-16 |

Equations solver categories